Chapter A statistical information system in support of job policies orientation - Martelli, Cristina (Proceedings e report, 2021)
A significant problem for labour market policies relies on the individuation of the most advisable skills to have and to enhance through focused training offers. Vocational training systems and institutions are called to answer the question posed by every person looking for a new job or professional opportunities: which are the skills-to-have to enhance the professional profile? Many efforts have been made to answer this question, mainly designing predictive models; however, these models are often limited to specific economic sectors and usually don't adopt a country-specific perspective. This paper proposes a recommendation system oriented to specific users: once that the user has described his/her skills profile, the system suggests the skills that, once got, will fit with the most frequent job vacancies. In this proposal perspective, the skills are proposed regardless of the economic sector, and they are compatible with the characteristics of the specific country labour market. In this contribution, we will focus on the Italian market; the recommendation system is based on the job ads published by Italian companies on various websites for both 2019 and 2020 after the skills required for each job offer have been mapped to one of the skills presented in the classification of European Skills/ competence, qualifications ad Occupations (ESCO).